2017
DOI: 10.1038/oncsis.2016.86
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the integrin/FAK signaling axis and c-Myc synergistically disrupts ovarian cancer malignancy

Abstract: Integrins, a family of heterodimeric receptors for extracellular matrix, are promising therapeutic targets for ovarian cancer, particularly high-grade serous-type (HGSOC), as they drive tumor cell attachment, migration, proliferation and survival by activating focal adhesion kinase (FAK)-dependent signaling. Owing to the potential off-target effects of FAK inhibitors, disruption of the integrin signaling axis remains to be a challenge. Here, we tackled this barrier by screening for inhibitors being functionall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 52 publications
4
37
0
Order By: Relevance
“…[41] FAK gene activation may exert important effects on cell growth and intracellular signal transduction pathways perturbed in response to certain neural peptides or to cell interactions with the extracellular matrix. Accumulating researches demonstrated that inhibition of FAK signalling contributed to suppressing cellular events in various types of cancers including melanomas, [42] ovarian cancer, [43] non-small-cell lung cancer [44] and breast cancer. [45] Our network analysis implicated several pathways including FAK signalling pathway through which EGCG might prevent breast cancer progression, involving cell proliferation and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…[41] FAK gene activation may exert important effects on cell growth and intracellular signal transduction pathways perturbed in response to certain neural peptides or to cell interactions with the extracellular matrix. Accumulating researches demonstrated that inhibition of FAK signalling contributed to suppressing cellular events in various types of cancers including melanomas, [42] ovarian cancer, [43] non-small-cell lung cancer [44] and breast cancer. [45] Our network analysis implicated several pathways including FAK signalling pathway through which EGCG might prevent breast cancer progression, involving cell proliferation and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…A central mediator of adhesion-dependent signaling, the role of FAK in mechanotransduction is regarded as being less in the generation of cellular tension and more in the transduction of signals downstream of mechanical cell-matrix interactions [65][66][67] . Nonetheless, its demonstrated importance in both functional mechanical signaling [68][69][70][71] and in the biology of EOC [72][73][74][75][76][77] prompted us to assess the effect of FAK inhibition on the EOC mechano-response. Unlike blebbistatin and fasudil, treatment of SKOV3 cells with PF-271 (also known as PF-562271), a potent and highly selective inhibitor of FAK, had no significant effect on cellular traction force ( Figure 8C and D) or stress fiber and phospho-MLC architecture ( Figure 8G and I), but significantly reduced phospho-FAK intensity while preserving or slightly enhancing focal adhesion size and aspect ratio ( Figure 8E and F), consistent with FAK's role in focal adhesion turnover 78 .…”
Section: A Mechanotransduction Pathway Comprising Rock Actomyosin Comentioning
confidence: 99%
“…In ovarian and prostate carcinoma mouse tumor models, FAK inhibition (VS-6063, defactinib) enhanced taxane-mediated tumor apoptosis (Kang, Hu et al, 2013, Lin, Lee et al, 2018. Additionally, inhibitors of FAK and Myc exhibit combinatorial activity in promoting HGSOC apoptosis in vitro (Xu, Lefringhouse et al, 2017). It remains uncertain whether gains in 8q24 encompassing PTK2 are associated with specific HGSOC cell phenotypes or responses to therapy, as determinants of FAK pathway dependence in tumors remain unknown.…”
Section: Introductionmentioning
confidence: 99%